Rural Residents’ Knowledge and Preventive Practices Regarding Dengue Fever: A Community-Based Survey in Sylhet - Mohammad Nurunnabi; Nazia Chowdhury; Md Ferdous Hasan; Tafhim Ahmed Rifat; Dania Siddiquah; Fazlur Rahim Kaiser (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Dengue is a mosquito-borne viral infection that poses significant public health challenges in Bangladesh. Understanding community knowledge and preventive practices is essential for effective dengue control. To assess the levels of knowledge and preventive practices regarding dengue infection among the rural residents of Sylhet district. Materials and methods: A community-based cross-sectional study was conducted from September 2023 to February 2024 in Rampasha village, Biswanath Upazila. A total of 200 adults aged ³ 18 years were purposively selected and data were collected through face-to-face interviews using a semi-structured questionnaire administered by 4th-year MBBS students. Results: Most participants had heard of dengue (86.0%) and knew mosquitoes transmit it (75.0%) but fewer identified Aedes as the vector (39.0%) or its feeding time (46.0%). Knowledge of preventive measures was high (93.0%) though use of repellents (1.0%) and aerosol sprays (8.5%) was low. Fever (79.5%) and fatigue (81.0%) were the most recognized symptoms. Preventive practices included mosquito net use (83.0%) removal of stagnant water (71.0%) covering water containers (67.0%) and neighborhood cleanliness (73.5%). Most respondents (64.5%) shared dengue information and 58.0% recognized paracetamol as the safest antipyretic. The majority of respondents had good knowledge (69.0%) and good preventive practices (60.5%) regarding dengue fever. Education and occupation were significantly associated with both knowledge (p=0.015 and 0.032, respectively) and practice levels (p=0.02 and 0.018, respectively) indicating that higher educational attainment and certain occupations (Homemakers, service holders) positively influence dengue-related knowledge and preventive behaviors. Conclusion: While rural residents of Sylhet show moderate to good knowledge and preventive practices regarding dengue, gaps remain in vector identification, symptom recognition and use of certain preventive measures. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 54-61